Strategi Pemerintah Republik Indonesia Dalam Penanganan Masalah Pelintas Batas Indonesia-Timor Leste - Aprilia Devita Mauk; Rina Tilon Nasalel Poni Luan; Adean Elisabet Berti Bano; Frouke Elsa Suhardjana; Yohanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
One of the borders that has a complicated governance issue is the border between Indonesia and Timor-Leste. The urgency to set up the Border Between Indonesia and Timor-Leste and the border crossers is based on much more complex historical reasons than the arrangement of Indonesia's borders with other countries. border governance policies between Indonesia and Timor-Leste are characterized by: border governance policies indicate a desire to adopt an integrated approach, governance practices tend to be fragmented where two very dominant approaches are the security approach and the socio-economic welfare approach. A border governance policy that ignores cultural identity variables leads to a reverse response, namely the use of cultural identity to challenge the country's dominant conception and policy in border governance. The phenomenon of